Web-Based Learning Media Wordwall in Fine Arts Learning to Increase Student Learning Motivation - Putri, Selviana Purnama; Husain, Muh. Saleh; Irfan, Irfan (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study aims to describe the application of web-based learning media, WordWall, to fine arts learning and to determine the extent to which the media can improve students' learning motivation. This study uses a survey method with a mixed-methods approach, namely a combination of qualitative and quantitative methods. The population and sample are 36 students of class XI B4 MAN 1 Bone. Data collection techniques include observation, interviews, questionnaires, and documentation. We carry out qualitative data analysis through reduction, presentation, and conclusion drawing, while we carry out quantitative data analysis through descriptive statistical calculations. The results of the study indicate that the application of WordWall through various interactive features has succeeded in creating a fun and interactive learning atmosphere. The results of the observation showed an increase in learning motivation from an average score of 3.7 to 4.8, while the results of the questionnaire showed an average score of 4.44, which is included in the "excellent" category. The four aspects in the ARCS model (attention, relevance, confidence, and satisfaction) have increased significantly. Therefore, WordWall has demonstrated its effectiveness in enhancing students' learning motivation in fine arts education.